Interactive Media Training for Teaching Explanatory Text Writing in Tanjung Jabung Timur Junior High School - Rahmawati, Sophia; Khalid, Kartini Aboo Talib @; Bambang, Siti Enik Mukhoiyaroh; D, Yusra; Akhyaruddin, Akhyaruddin; Pratama, Deri Rachmad; Adiyadmo, Dimas Anugrah; Saputra, Ade Bayu; Iqroni, David; Yanto, Anggel Hardi (Jurnal Karya Abdi Masyarakat, 2025)
Indonesian language teachers at junior high schools in Tanjung Jabung Timur Regency face challenges in teaching explanatory text writing due to limited use of interactive digital learning media and inadequate integration of technology into pedagogy. This community engagement program aimed to enhance teachers’ competence through training based on the Technological Pedagogical Content Knowledge (TPACK) framework, with a focus on the Canva platform. The program involved 30 Indonesian language teachers from several junior high schools and was implemented through structured activities, including needs assessment, material delivery, collaborative discussions, hands-on media development, and evaluation using pretest and posttest instruments. The results showed a significant improvement in teacher competence, indicated by a mean score difference of −15.433, a significance value of 0.000 (p < 0.05), and a very large effect size (Cohen’s d = 2.648). These findings confirm that the training effectively improved teachers’ ability to design creative, interactive, and curriculum-aligned digital learning media for teaching explanatory texts. The novelty of this program lies in the contextual integration of the TPACK framework with digital media training oriented toward explanatory writing and local content, supporting the technology-enhanced implementation of the Merdeka Curriculum and providing a replicable model for similar teacher training initiatives.